Comportamento de pilares mistos preenchidos com concreto de resíduos de concreto submetidos a compressão axial centrada: efeito do teor de substituição e da forma de aplicação da força - Gerin, Mayara Turi (2020)
Seeking to mitigate the environmental impact of civil construction, investigations focused on concrete waste use in the production of new concrete are pushing the Brazilian researches. However, despite significant advances were made in the material composition resulting in feasible tensile strengths, this concrete, in general, still has poorer mechanical properties than concrete from natural aggregates, especially regarding to deformability. On the other hand, it is known that the confinement effect may improve such concrete mechanical properties. In this context, the recycled aggregates concrete filled steel tube appears as an option for the application of recycled aggregates concrete. Therefore, the main objective of this work was to analyze the behavior of recycled aggregates concrete filled steel tube submitted to concentric axial compression and the confinement effect provided by the steel tube to the concrete core. For this, we evaluated i) the influence of the substitution content of natural coarse aggregates by recycled aggregates concrete and ii) different methods of load application, one in the concrete core and the other in the composite section of the column. To do so, firstly, concrete characterization was performed to analyze the effects of total and partial replacement of natural aggregates by recycled concrete as coarse aggregates. Secondly, physical models of short circular columns filled with recycled aggregates concrete were tested and the results were compared to models filled with natural aggregate concrete. The method of load application significantly altered the response of the confined concrete, since the confinement stresses are developed at different times in each situation analyzed. The specimens with load application on the concrete core, although not commonly used in designing, helped to understand the effect of confinement of the concrete core of filled columns. Regardless of the aggregate type, the concrete mechanical properties ruled the confinement effect provided by the steel tube, and consequently, the behavior of the columns. Moreover, the substitution of natural aggregates for recycled concrete aggregates alone did not present significant effect on the behavior of the concrete filled steel tube nor on the deformations of the materials. It suggests that the investigated substitution may be viable for application in such structural elements.